THE CRYPTOGRAPHY TECHNIQUE ON THE BASIS OF THE TRIGONOMETRIC FUNCTION OF TWO ARGUMENTS - Valery Petrovich Mochalov; Natalia Yurievna Bratchenko; Sergey Vladimirovich Yakovlev; Darya Valeryevna Guseva (Современная наука и инновации, 2022)
The cryptography technique with use of a trigonometric function of two arguments was offered. The implementation of the developed method is given in a specific example. Comparing with the existing implementations on the basis of the use of one argument defines the offered method as more stable against cracking